1988
DOI: 10.1007/bf00257364
|View full text |Cite
|
Sign up to set email alerts
|

A sensitive high-performance liquid chromatographic assay for melphalan and its hydrolysis products in blood and plasma

Abstract: A sensitive high-performance liquid chromatographic assay has been developed for the measurement of the alkylating cytostatic drug melphalan (4-[bis(2-chloroethyl)amino]-L-phenyl-alanine, or L-phenylalanine-mustard, L-PAM) and its two hydrolysis products, monohydroxy melphalan (MOH) and dihydroxy melphalan (DOH). A reversed-phase phenyl column and a mobile phase consisting of acetonitrile/citrate buffer made possible an isocratic separation and quantification. N,N-[bis(2-hydroxy-ethyl)]toluidine has been synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…31 Melphalan obtained from Sigma (Deisenhofen, Germany) and the internal standard propylparaben (Sigma) were separated on a reversed-phase C 18 column (LiChrospher 100 RP-18, 5 mm particle size; Merck, Darmstadt, Germany) with a corresponding precolumn (LiChroCART 4-4, LiChrospher 100 RP-18 (5 mm); Merck). Concentrations of melphalan in plasma were measured with an isocratic highperformance liquid chromatography with fluorescence detection set to 270 nm (excitation) and 365 nm (emission) based on published methods.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Melphalan obtained from Sigma (Deisenhofen, Germany) and the internal standard propylparaben (Sigma) were separated on a reversed-phase C 18 column (LiChrospher 100 RP-18, 5 mm particle size; Merck, Darmstadt, Germany) with a corresponding precolumn (LiChroCART 4-4, LiChrospher 100 RP-18 (5 mm); Merck). Concentrations of melphalan in plasma were measured with an isocratic highperformance liquid chromatography with fluorescence detection set to 270 nm (excitation) and 365 nm (emission) based on published methods.…”
Section: Methodsmentioning
confidence: 99%
“…Concentrations of melphalan in plasma were measured with an isocratic highperformance liquid chromatography with fluorescence detection set to 270 nm (excitation) and 365 nm (emission) based on published methods. 31 Melphalan obtained from Sigma (Deisenhofen, Germany) and the internal standard propylparaben (Sigma) were separated on a reversed-phase C 18 column (LiChrospher 100 RP-18, 5 mm particle size; Merck, Darmstadt, Germany) with a corresponding precolumn (LiChroCART 4-4, LiChrospher 100 RP-18 (5 mm); Merck). The mobile phase was phosphate buffer (0.02 M, pH 4) and methanol (58:42, v/v).…”
Section: Methodsmentioning
confidence: 99%
“…In reports of ILP it is remarkable that the volume of perfusate, which critically determines the effective concentration of melphalan, has been so neglected. In fact, the volume of prime is often omitted in reports (Storm & Morton, 1985;Schraffordt Keeps et al, 1987;Sugarbaker & McBride, 1976;Mikhail et al, 1984;Rege et al, 1983), even in studies of melphalan pharmacokinetics (Hafstrom et al, 1984;Osterheld et al, 1988).…”
Section: Pharmacokinetics Of Bolus Administrationmentioning
confidence: 99%
“…When melphalan was administered to cancer patients, its monohydroxy metabolite, 3.274, and its dihydroxy metabolite, 3.275, were detected in the plasma where their combined AUC (area under the plasma-concentration-time curve) amounted to ca. 30% of the AUC of the drug [179]. In vitro studies have shown that melphalan reacts by the general mechanism discussed above, namely via a first and second aziridinium intermediate.…”
Section: Fig 332 Thismentioning
confidence: 98%